PERBANDINGAN ELEVASI DASAR SUNGAI BERDASARKAN HASIL ANALISIS PADA DEM DRONE, DEMNAS dan DEM SRTM - Zufrimar, Zufrimar; Zainal, Edwina (SIGMA TEKNIKA, 2023)
Digital elevation models (DEMs) are essential to accurately predict river cross-section in the watershed. Technological developments of unmanned aerial vehicles (UAVs) or drone has received a lot of attention in various research field to get the latest information from the area, because of its mobility, high resolution, and low cost, so it can be a competitive alternative to produce maps with precise georeferences. However, this has not been tested so far. In this study, We evaluated the accuracy of the DEMs generated from UAV imagery by comparing it to DEMNAS, DEM SRTM, and direct topographic measurements. We performed regression analysis on the river bed elevation of the Kuranji River Padang, where the river bed elevation is the result of the analysis of each DEM. The result found that for river bed elevation of the DEM Drone performed competitively to DEMNAS with the correlation test value (r) were 0,992 and 0.954, respectively. The result of the DEM SRTM analysis has a wider range of data variations than the DEM Drone and DEMNAS.